Osteoarticular tissue infection and development of skeletal pathology in murine brucellosis - Diogo M. Magnani; Elizabeth T. Lyons; Toni S. Forde; Mohammed T. Shekhani; Vyacheslav A. Adarichev; Gary A. Splitter (The Company of Biologists, 2013)
SUMMARY Brucellosis, a frequent bacterial zoonosis, can produce debilitating chronic disease with involvement of multiple organs in human patients. Whereas acute brucellosis is well studied using the murine animal model, long-term complications of host-pathogen interaction remain largely elusive. Human brucellosis frequently results in persistent, chronic osteoarticular system involvement, with complications such as arthritis, spondylitis and sacroiliitis. Here, we focused on identifying infectious sites in the mouse that parallel Brucella melitensis foci observed in patients. In vivo imaging showed rapid bacterial dispersal to multiple sites of the murine axial skeleton. In agreement with these findings, immunohistochemistry revealed the presence of bacteria in bones and limbs, and in the lower spine vertebrae of the axial skeleton where they were preferentially located in the bone marrow. Surprisingly, some animals developed arthritis in paws and spine after infection, but without obvious bacteria in these sites. The identification of Brucella in the bones of mice corroborates the findings in humans that these osteoarticular sites are important niches for the persistence of Brucella in the host, but the mechanisms that mediate pathological manifestations in these sites remain unclear. Future studies addressing the immune responses within osteoarticular tissue foci could elucidate important tissue injury mediators and Brucella survival strategies.